2021
DOI: 10.1051/0004-6361/202141581
|View full text |Cite
|
Sign up to set email alerts
|

Granular mechanics simulations of collisions between chondritic aggregates

Abstract: Context. Collisions of dust aggregates are relevant for the evolution of protoplanetary disks. Aims. While in the past interest focused on aggregates composed of monodisperse grains, here we study the collision of chondritic aggregates, in which – besides a majority of dust grains – larger chondrules are embedded. Methods. We use granular-mechanics simulations to study collisions of chondritic aggregates. Results. Low-velocity collisions lead to pancake-shaped deformations of the fused cluster accompanied by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The collisional behavior of dust aggregates has been reported in a large number of studies based on both laboratory experiments (e.g., Blum & Wurm 2008;Güttler et al 2010;Shimaki & Arakawa 2012;Brisset et al 2016Brisset et al , 2017Schräpler et al 2018Schräpler et al , 2022Fritscher & Teiser 2021) and numerical simulations (e.g., Wada et al 2007Wada et al , 2008Wada et al , 2009Wada et al , 2013Paszun & Dominik 2009;Seizinger et al 2013;Sirono & Ueno 2017;Umstätter & Urbassek 2020, 2021aHasegawa et al 2021;Sirono & Kudo 2021). It is known that the threshold collision velocity for the fragmentation of dust aggregates, v fra , depends on material properties of constituent particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The collisional behavior of dust aggregates has been reported in a large number of studies based on both laboratory experiments (e.g., Blum & Wurm 2008;Güttler et al 2010;Shimaki & Arakawa 2012;Brisset et al 2016Brisset et al , 2017Schräpler et al 2018Schräpler et al , 2022Fritscher & Teiser 2021) and numerical simulations (e.g., Wada et al 2007Wada et al , 2008Wada et al , 2009Wada et al , 2013Paszun & Dominik 2009;Seizinger et al 2013;Sirono & Ueno 2017;Umstätter & Urbassek 2020, 2021aHasegawa et al 2021;Sirono & Kudo 2021). It is known that the threshold collision velocity for the fragmentation of dust aggregates, v fra , depends on material properties of constituent particles.…”
Section: Introductionmentioning
confidence: 99%
“…Most of numerical simulations of collisions between dust aggregates did not include the viscous dissipation force (e.g., Dominik & Tielens 1997;Wada et al 2007Wada et al , 2008Wada et al , 2009Hasegawa et al 2021). Although a small number of studies (e.g., Seizinger et al 2013;Umstätter & Urbassek 2021a, 2021b introduced the viscous dissipation force to their numerical simulations of collisions between dust aggregates, the dependence of v fra on the strength of viscous dissipation force is still poorly understood. For head-on collisions between equal-mass dust aggregates, Umstätter & Urbassek (2021b) reported that the threshold velocity increases with increasing the strength of viscous dissipation force; however, when we consider oblique collisions, whether the viscous dissipation helps the collisional growth of dust aggregates is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we must give an explanation for the co-existence of rimmed and unrimmed chondrules in the context of FGR formation. Several mechanisms were proposed so far: Tomeoka & Ohnishi (2010) claimed that unrimmed chondrules have lost FGRs during the brecciation process on their parent bodies, whereas Umstätter & Urbassek (2021) proposed that unrimmed chondrules were formed via collisional fragmentation of chondritic aggregates in the solar nebula.…”
Section: Co-existence Of Rimmed and Unrimmed Chondrulesmentioning
confidence: 99%
“…However, much lower φ agg does not necessarily mean much lower φ rim because porous aggregates can be compressed when they accrete onto chondrules. Further more, compound aggregates (Arakawa, 2017;Matsumoto et al, 2019) composed of rimmed chondrules and matrix aggregates might suffer ejection of chondrules through collisions (Arakawa, 2017;Umstätter and Urbassek, 2021). This mechanism can be one of the causes of unrimmed chondrules (e.g Simon et al, 2018).…”
Section: Erosion Fragmentation Sputtering and Compaction Of Fgrsmentioning
confidence: 99%